أثر أزمة الكوفيد على تحفيز استخدام وسائل الدفع الإلكتروني ومساهمته في الاقتصاد الجزائري - معرف، نورة; دربوش، محمد الطاهر (جامعة الوادي University of Eloued, 2025)
This research paper aims to illuminate the justifications that led to the transmission of the health shock, most notably the Covid epidemic to the financial sector and electronic payment methods. It also aims to reveal details of the sensitivity of the global economy to imbalances and the reasons for their acceleration during the pandemic by shedding light on some countries in general and Algeria in particula، In this researchpaper, we relied on the descriptive analytical approach for the purpose of detailing the merits of the crisis. We used the historical approach for the purpose of inferring the conditions of instability setbacks. As for the applied aspect, it was a standard study based on the EViews program for standard analysis of the time series under study ،This research paper concluded that Covid19 once again demonstrated the fragility of the economic system in general and the financial system in particular, as the global economy recorded the largest shock after the 2008 financial crisis
The impact of the Covid crisis on stimulating the use of electronic payment methods and its contribution to the Algerian economy Standard study for the period (2019-2024)
Keywords: أزمة صحية; اقتصاد; كوفيد 19; تداعيات مالية; وسائل الدفع الإلكتروني; health crisis; economy; Covid-19; financial repercussions; electronic payment methods